2013
DOI: 10.1155/2013/240108
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Androgen Deprivation Therapy for Prostate Cancer: Prevention and Management

Abstract: The prostate is an androgen-dependent organ. The increase, growth, homeostasis, and function of the prostate largely depend upon the intraprostatic and serum concentrations of androgens. Therefore, androgens are essential for the physiologic growth of prostatic epithelium. Prostate cancer, the second leading cause of death for men, is also androgen dependent, and androgen suppression is the mainstay of treatment for advanced and metastatic disease. In the state of metastatic disease, androgen suppression is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Many neural centers in the brain, including those critical to cognitive processes, have estrogen receptors, as noted above . This suggests that supplemental E2 may be of some benefit for men on ADT . Estrogen taken orally increases the risk of thromboembolic events and gynecomastia .…”
Section: Introductionmentioning
confidence: 97%
“…Many neural centers in the brain, including those critical to cognitive processes, have estrogen receptors, as noted above . This suggests that supplemental E2 may be of some benefit for men on ADT . Estrogen taken orally increases the risk of thromboembolic events and gynecomastia .…”
Section: Introductionmentioning
confidence: 97%
“…As well as emotional distress on receipt of diagnosis and prognosis (Jonsson et al, 2009), men with advanced prostate cancer experience on-going impairments in psychosocial functioning, for example in relation to the physical consequences of disease progression such as pain and fatigue (De Sousa et al, 2012). The limited research into psychological well-being in men with advanced prostate cancer tends to focus on the sideeffects of ADT, for example clinical reports of depression and mood swings relating to testosterone depletion (Sountoulides & Rountos, 2013). Qualitative research has shown that physical side effects such as hot flushes, sexual dysfunction and breast swelling are linked to loss of identity, feminisation, feelings of self-loathing and reduced self-esteem (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ADT can involve orchidectomy, luteinizing hormone‐releasing hormone (LHRH) agonists, gonadotrophin‐releasing hormone (GnRH) antagonists and anti‐androgens . ADT induces a significant reduction in serum testosterone that commonly results in reduced sexual desire and sexual function .…”
Section: Introductionmentioning
confidence: 99%